COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE COMPANY BEFORE AND AFTER MERGER AND ACQUISITION TO ENTRANCHMENT MANAGEMENT - Nila Pratiwi; Hasmaynelis Fitri; Inneke Sastila Murni (Jurnal Apresiasi Ekonomi, 2018)
The purpose of this study to determine and analyze the extent to which the financial performance owned by manafaktur companies listed on the Stock Exchange, in an effort to acquire and merger is done to provide sustainability or going concern. This performance appraisal is measured by using financial ratios including Net Profit Margin (NPM), Return On Assets (ROA), Return On Equity (ROE), Debt to Equity Ratio (DER). form of normality test and paired sample T-Test. The research shows that (1) Net Profit Margin (NPM) there is a difference between before and after mergers and acquisitions in manufacturing companies listed BEI period 2011-2015, (2) Return On Assets (ROA) there is difference between before and after merger and (3) Return On Equity (ROE) there is a difference between before and after mergers and acquisitions in BEI listed manufacturing companies for the period 2011-2015, (4) Debt to Equity Ratio (DER ) there is a difference between before and after mergers and acquisitions on manufacturing companies listed BEI period 2011-2015. Keywords :  Net Profit Margin (NPM), Return On Assets (ROA), Return On Equity (ROE), Debt to Equity Ratio (DER).